The failures of public art and participation - Cartiere, Cameron; Schrag, Anthony (Routledge, 2023)
This collection of original essays takes a multi-disciplinary approach to explore the theme of failure through the broad spectrum of public art and social practice. The anthology brings together practicing artists, curators, activists, art writers, administrators, planners, and educators from around the world to offer differing perspectives on the many facets of failure in commissioning, planning, producing, evaluating and engaging communities in the continually evolving field of art in the public realm. As such, this book offers a survey of currently unexplored and interconnected thinking, and provides a much-needed critical voice to the commissioning of public and participatory arts. The volume includes case studies from the U.K., the U.S., China, Cuba, and Denmark, as well as discussions of digital public art collections. The Failures of Public Art and Participation will be of interest for students and scholars of visual arts, design and architecture interested in how art in the public realm fits within social and political contexts"--